Cyber safety in e-learning: The effects of cyber awareness and information security policies with moderating effects of gender and experience levels among e-learning students - Oroni, Chrispus Zacharia; Xianping, Fu; Ndunguru, Daniela Daniel; Ani, Arsenyan (Education and information technologies, 2025)
In recent times, the rapid growth of e-learning has brought about increased concerns regarding cybersecurity risks within digital learning environments. Despite the growing importance of cybersecurity awareness among e-learning students, there is limited research on the factors that influence students' understanding and adherence to cyber safety practices. This study investigates the relationship between e-learning engagement, cybersecurity awareness, and cyber safety practices, with a focus on the moderating roles of gender and e-learning experience. The research emphasizes the need to consider demographic factors such as gender and experience level when designing cybersecurity interventions for online learners. The investigation uses structural equation modeling to analyze how engagement in e-learning platforms influences students' cybersecurity awareness and their adherence to security protocols. Among the key findings from SEM, the study reveals that e-learning engagement positively impacts cybersecurity awareness, with gender and experience level acting as significant moderators. However, the study also found that experienced learners may initially face challenges in applying security protocols effectively, though their understanding improves over time with continued engagement. In addition, the research found that students with higher e-learning engagement are more likely to adopt cyber safety practices and comply with information security policies. Interestingly, the results suggest that educational institutions should tailor cybersecurity programs to address the unique needs of students based on their gender and experience levels. Furthermore, our research can inform future policies and interventions aimed at promoting cybersecurity awareness among e-learning students, ultimately contributing to safer and more secure digital learning environments.